Pattern of expression of Toll like receptor (TLR)-3 and -4 genes in drug-naïve and antipsychotic treated patients diagnosed with schizophrenia. (March 2020) - Balaji, Renu; Subbanna, Manjula; Shivakumar, Venkataram; Abdul, Fazal; Venkatasubramanian, Ganesan; Debnath, Monojit
Highlights: TLR pathway might play important role in pathobiology of schizophrenia. TLR4 gene expression is upregulated in drug naïve schizophrenia patients. Antipsychotics don't alter TLR3 and TLR4 gene expression in schizophrenia patients. Abstract: Toll like receptors (TLRs), a class of conserved immune molecules are crucially involved in initiating innate immune response to infection. TLR activation and subsequent inflammation are linked to pathogenesis of many brain disorders. Preliminary studies indicate a possible role of TLR-driven immuno-inflammatory responses in schizophrenia. However, gene expression data of TLRs in drug-naïve as well as antipsychotic treated patients diagnosed with schizophrenia are albeit limited. In this study, expression profile of TLR3 and TLR4 genes in peripheral blood mononuclear cells (PBMCs) was compared between drug-naïve patients diagnosed with schizophrenia ( N  = 31) and healthy controls ( N  = 30). In addition, the pattern of expression of TLR3 and TLR4 genes were also examined after three months of antipsychotic medication in patients. Compared to healthy controls, gene expression levels of only TLR4 ( F  = 3.87, p  = 0.05, ηp 2  = 0.06), not TLR3 ( F  = 0.17, p  = 0.71, ηp 2  = 0.003) was significantly up-regulated in drug-naïve patients. The changes in the levels of gene expression of TLR3 ( t  = 0.09, p  = 0.93, d  = 0.02) and TLR4 ( t  = 0.29, p  = 0.77, d  = 0.06) before and after antipsychotic medication were not found to be statistically significant. This finding suggests possible contribution of TLR4 in immunopathogenetic pathway of schizophrenia.